Examining the prevention approach in National Dementia Plans from European and North American countries - Andreoletti, Mattia; Blasimme, Alessandro (Frontiers in Dementia, 2025)
Objectives: This paper aims to provide a comprehensive review of National Dementia Plans (NDPs) from selected European and North American countries, focusing on the distinct prevention strategies outlined and the approaches employed for reducing dementia risk. Method: The sample consisted of 16 NDPs from Austria, Canada, Finland, France, Germany, Greece, Ireland, Italy, Liechtenstein, Luxembourg, Malta, the Netherlands, Spain, Switzerland, the UK, and the USA. These NDPs were retrieved from the Alzheimer's Disease International (ADI) database, with regular updates checked on official governmental websites. A qualitative analysis was conducted to identify common themes related to the vision, goals, and corresponding actions and measures within these strategies. Results: Our analysis revealed that dementia prevention is a strategic goal for most of the countries studied. Common actions identified include the identification of risk factors, advancing research, promoting healthy aging, increasing public awareness, and encouraging lifestyle interventions. Conclusion: We discuss the limitations and challenges of these actions, and more broadly, of the NDPs in relation to the recent literature on the most effective approaches to preventing dementia. We suggest adopting a more "horizontal" approach to dementia prevention, which current NDPs overlook in favor of "vertical" paradigms.